The Influence of Organizational Culture, Organizational Commitment, on Motivation and Job Satisfaction of Employees and Lecturers at Muhammadiyah University of Palu - Dirwan, Dirwan; Rajindra, Rajindra; Farid, Farid; Henni Mande; Nursiah, Nursiah; Ali Supriadi (Universitas Muhammadiyah Palu, 2024)
In the context of the world of work, the influence of organizational culture and organizational commitment on motivation and job satisfaction is an increasingly relevant research topic. Organizational culture reflects the values, norms, and beliefs held together by members of an organization, while organizational commitment reflects the level of attachment and loyalty of individuals to the organization where they work. These two factors are believed to have an important role in shaping employee motivation and job satisfaction. Therefore, this study aims to analyze the influence of organizational culture and organizational commitment on the motivation and job satisfaction of employees and lecturers in an organizational environment. This research is a quantitative study. This research was conducted at the Muhammadiyah University of Palu, using 129 respondents consisting of employees and lecturers as research samples. The data analysis used in this study was through structural equation modeling (SEM) analysis. The results of this study indicate that organizational culture and organizational commitment have a positive and significant effect on motivation and job satisfaction. Furthermore, organizational culture and organizational commitment have a positive and significant effect on job satisfaction mediated by work motivation. By creating a motivating and satisfying work environment, universities can improve academic and administrative performance, which in turn will improve the reputation and attractiveness of the institution to prospective students and other stakeholders.